Cationic Chalcogenoviologen Derivatives for Photodynamic Antimicrobial Therapy and Skin Regeneration. Issue 59 (28th August 2019) - Zhou, Kun; Tian, Ran; Li, Guoping; Qiu, Xinyu; Xu, Letian; Guo, Mengying; Chigan, Dongdong; Zhang, Yanfeng; Chen, Xin; He, Gang
Abstract: A series of water‐soluble cationic chalcogenoviologen‐based photosensitizers for photodynamic antimicrobial therapy (PDAT) is reported. The Se‐containing derivatives (SeMV 2+ ) 5 b and 6 b showed good antimicrobial activities due to the presence of chalcogen atoms and a cationic scaffold. The former efficiently enhanced the generation of reactive oxygen species (ROS), and the latter facilitated the ROS delivery to bacteria, resulting in their death. Interestingly, alkyl‐modified photosensitizers showed higher antimicrobial activities than commonly reported photosensitizers with quaternary ammonium (QA) groups. In particular, the SeMV 2+ (6 b ) with excellent antibacterial activities efficiently promoted the healing of infected wounds in mice. Simple yet novel, nontoxic and biocompatible chalcogenoviologens provided a promising strategy to develop new efficient photosensitizers for photodynamic antimicrobial therapy and skin regeneration. Abstract : A series of water‐soluble cationic chalcogenoviologen‐based photosensitizers for photodynamic antimicrobial therapy (PDAT) is reported. One SeMV 2+ in particular showed excellent antibacterial activities and efficiently promoted the healing of infected wounds in mice (see figure).